Identification of human nephron progenitors capable of generation of kidney structures and functional repair of chronic renal disease. Issue 10 (2nd September 2013) - Harari‐Steinberg, Orit; Metsuyanim, Sally; Omer, Dorit; Gnatek, Yehudit; Gershon, Rotem; Pri‐Chen, Sara; Ozdemir, Derya D.; Lerenthal, Yaniv; Noiman, Tzahi; Ben‐Hur, Herzel; Vaknin, Zvi; Schneider, David F.; et al.
<x xml:space="preserve">Abstract</x> Identification of tissue‐specific renal stem/progenitor cells with nephrogenic potential is a critical step in developing cell‐based therapies for renal disease. In the human kidney, stem/progenitor cells are induced into the nephrogenic pathway to form nephrons until the 34 week of gestation, and no equivalent cell types can be traced in the adult kidney. Human nephron progenitor cells (hNPCs) have yet to be isolated. Here we show that growth of human foetal kidneys in serum‐free defined conditions and prospective isolation of NCAM1+ cells selects for nephron lineage that includes the SIX2‐positive cap mesenchyme cells identifying a mitotically active population with in vitro clonogenic and stem/progenitor properties. After transplantation in the chick embryo, these cells—but not differentiated counterparts—efficiently formed various nephron tubule types. hNPCs engrafted and integrated in diseased murine kidneys and treatment of renal failure in the 5/6 nephrectomy kidney injury model had beneficial effects on renal function halting disease progression. These findings constitute the first definition of an intrinsic nephron precursor population, with major potential for cell‐based therapeutic strategies and modelling of kidney disease.